Integrative taxonomy of a new species of the genus Pyrrhalta Joannis, 1865 (Coleoptera: Chrysomelidae: Galerucinae) from Southern Vietnam, with a key to Vietnamese species - Dinh, Nguyen Thi; Gómez-Zurita, Jesus (Academia Journal of Biology, 2025)
A new species of genus Pyrrhalta (Chrysomelidae: Galerucinae), Pyrrhalta dorsotibialis n. sp., is described based on specimens from the Nui Chua National Park in southern Vietnam. Color photographs of habitus and body details, as well as an identification key for all Vietnamese species of the genus Pyrrhalta are provided. Moreover, Menippus gressitti Lee, Bezdĕk & Suenaga and Pyrrhalta prokofievi Skomorokhov are reported from Nui Chua, the latter as a remarkable finding, considering that the species was only known from the Con Dao Island. The availability of cox1 DNA sequence data for these species in the Nui Chua Park allowed for a preliminary assessment of local phylogenetic diversity of this group compared with other homologous sequences publicly available for Pyrrhalta and the related genus Menippus. The two species currently recorded in the park seem to belong to at least two divergent phylogenetic lineages in the genus and highlighting the importance of the park for conservation of distant evolutionary branches of Pyrrhalta.